Electrochemical effect of graphite fluoride modification on Li-rich cathode material in lithium ion battery. Issue 1 (January 2019) - Jiang, Bing; Luo, Bi; Li, Jingru; Peng, Peng; Chen, Jiewei; Chu, Lihua; Li, Yingfeng; Li, Meicheng
Abstract: Recently, Li-rich layered structure has been used in the cathode of lithium ion batteries because of its high specific capacity. However, this structure still has some problems including large irreversible capacity loss, significant deterioration of cycling performance and poor rate property. Therefore, in our study, graphite fluoride is used to modify the surface of Li1.14 Ni0.133 Co0.133 Mn0.544 O2 through a facile solvent evaporating method. Due to conversion reaction of the graphite fluoride, the huge discharge capacity compensation during the first discharging can improve the coulombic efficiency significantly. As reaction products, the layer of LiF@carbon reduces the interfacial reactions and increases the reversible capacity. After modification by graphite fluoride, the discharge capacities are improved by 22% from 266 to 325 mAh g −1 at 0.1 C, and 13% at 2 C. After 100 cycles, the discharge capability at 1 C is increased by 13% from 180 to 203 mAh g −1 .